Good Governance in Upper Northeast Sub-District Administration Organization (SakonNakhon, NakhonPhanom, Mukdahan) - Kaensuwan, Muthuda; Kosonkittiumpo, Assoc. Prof. Dr. Saowalak; Phosing, Assoc. Prof. Dr. Pakdee Phosing; Poosri, Assoc. Prof. Dr. Somjet (Journal for Developing the Social and Community, 2018)
The purpose of this research were 1) study level of good governance, to study factors that affect succeed, to suggest guideline ; in Upper Northeast Sub-district Administration Organization (SakonNakhon, NakhonPhanom, Mukdahan). Research methodology divided into 2 phases : The first to study level and factor that affect succeed in Good Governance by demonstrated hypothesis and verify theoretical relationship equation. Number of sample according to Yamane’s equation (1973 : 727) was 128 in total. The data was collected by questionnaire that has 0.97 of reliability. The data then was analyzed by using frequency, percentage, mean, standard deviation, Pearson’s product moment correlation coefficient and multiple regression analysis. The second phase was to study guidelines of good governance. Target group include expert, academician, official chief of local government, selectively chose specific 20 participants by organize a group discussion about guideline and verify with 5 professionals who has participate in governance; analyzing data for appropriate asseverate and suggest adjusted guideline of good governance. The findings of the research included : 1) Level of Good Governance in overall were at high level Aspect had 4.19, 4.17, 4.14, 4.13 mean score respectively as following : demand response of people, development of knowledge and evaluation in official; achievement of mission; efficiently and worthiness of mission; happiness of people. 2) Factors that affect good governance guideline included : Mission, Policy and strategy; Leadership and Participation; Politics in the Organization. Regression coefficient in raw score were 0.316, 0.227, 0.230, 0.194 ; in standard score were 0.320, 0.271, 0.262, 0.215 respectively. This 4 predictive variables can predict 94.70% of good governance guidelines with statistically significant at.05 level and 3) An appropriate guideline of good governance had to develop moral principle in executive manager of Local Government to plant will-power in profession, organize moral promotion course for everyone in Local Government and allow people or an organization to participate in the progress operation; by many in a commission appearance or the participant known all information thoroughly in administration so that people may receive benefit literally and area that had develop reliability and faith increases efficient in operation such as flexibility in operation, decentralization fairly, build relationship in the organization, create sprit to use resources worthily.